Skewed X Chromosome Inactivation and Female Preponderance in Autoimmune Thyroid Disease: An Association Study and Meta-Analysis - Simmonds, Matthew J.; Kavvoura, Fotini K.; Brand, Oliver J.; Newby, Paul R.; Jackson, Laura E.; Hargreaves, Chantal E.; Franklyn, Jayne A.; Gough, Stephen C. L. (The journal of clinical endocrinology and metabolism, 2014)
Context:A number of small data sets have suggested a potential role for skewed X chromosome activation (XCI), away from the expected 50:50 parent of origin ratio, as an explanation for the strong female preponderance seen in the common autoimmune thyroid diseases (AITD), Graves' disease (GD), and Hashimoto's thyroiditis (HT).Objective:The objective of the study was to confirm a role for XCI skewing as a potential explanation for the strong female preponderance seen in AITD.Design:The design of the study was to screen XCI in the largest GD, HT, and control case-control cohort and family cohort to date and undertake a meta-analysis of previous AITD XCI reports.Setting:The study was conducted at a research laboratory.Patients:Three hundred and nine GD, 490 HT, and 325 female UK Caucasians controls, 273 UK Caucasian GD families, and a meta-analysis of 454 GD, 673 HT, and 643 female Caucasian controls were included in the study.Main Outcome Measures:Case-control and family-based association studies and meta-analysis were measured.Results:Skewed XCI was observed with GD [odds ratio (OR) 2.17 [95% confidence interval (CI) 1.43–3.30], P = 2.1 × 10−4] and a trend toward skewing with HT (P = .08) compared with the control cohort. A meta-analysis of our UK data and that of four previous non-UK Caucasian studies confirmed significant skewing of XCI with GD [OR 2.54 (95% CI 1.58–4.10), P = 1.0 × 10−4, I2 = 30.2%] and HT [OR 2.40 (95% CI 1.10–5.26), P = .03, I2 = 74.3%].Conclusions:Convincing evidence exists to support a role for skewed XCI in female subjects with AITD, which may, in part, explain the strong female preponderance observed in this disease.